Peran Kepemimpinan dalam Kepuasan Kerja Karyawan dalam Sebuah Perusahaan - dedy syahyuni (Universitas Bina Sarana Informatika, 2017)
Leadership is a capability that is owned by someone to influence other in order to achieve the objective of the organization or company. Leadership is also a process influencing other and done continuously. So Leadership is one thing that must remain in the process of planning, implemetation, setting and goal achievement in organization. In addition to serving to achieve company goals, leadership is also impacting many other fields within the company, one of them is job satisfaction. In some cases, the existence of the workers who got a good compensation and rewards from the company but suffered demotivation and decreased job satisfaction due to poor levels of leadership from his superiors. The purpose of this study was to determine the relationship between the leadership with job satisfactionKeyword: Job Satisfaction, Influence, Leadership